Evaluasi dan Pengembangan Capaian Kompetensi Lulusan Melalui Tracer Study - Khaerul Aqbar (Adaara: Jurnal Manajemen Pendidikan Islam, 2021)
This study aimed to recognize the situation of alumni of STIBA Makassar in the working world and the utilization of competencies obtained during their studies in University College of Islamic Sciences and Arabic Language (STIBA). This study employed survey as a type of research, and then was described in a descriptive qualitative way. The stages were simply: 1) Development of concepts and instruments of survey; 2) data collection; and 3) data analysis and report. The results showed that: 1) Most alumni of STIBA Makassar, as many as 71%, have entered working world, while the other 29% do not or do not yet worked; 2) Competency achievements of alumni of STIBA Makassar in general are in the good and high category; and 3) The main learning methods used at STIBA Makassar based on the answers of alumni respondents are still dominated by lectures, field work, and discussions.